Conceptualizing a Management Model of Islamic Education for Muallafs in Malaysia: Fundamental Inputs for Improvement - Abu Hasan, Ashari (MENARA : Journal of Islamic and Contemporary Issues, 2025)
This paper explores the management of the education of Muallafs, or the Muslim converts in the state of Selangor, Malaysia in the attempt to understand further the education efforts by the relevant bodies tasked at monitoring the welfare and well-being of the converts. The aims of the study are to understand the challenges faced by the Muslim Welfare Organization Malaysia or better known as PERKIM (Pertubuhan Kebajikan Islam Malaysia) and the teachers in their efforts to educate the Muallafs whilst also investigating the root causes leading to the challenges faced by the Muallafs themselves. Ultimately, the study aims to conceptualize a management model of Islamic education specifically for the Muallafs. Using the qualitative approach, in-depth interviews with the managers of PERKIM and the teachers employed by PERKIM to understand their views were carried out. Subsequently the Muallafs’ perspectives were also gathered through Focus group interviews, and these were cross analysed with the responses of the managers and the teachers. Essentially, purposive sampling method used was able to select the key informants for the study. The findings of the analyses led to the conceptualization of the Management Model of Islamic Education for the Muallafs where the focal point of the model were the converts’ psychological, spiritual and physical wellbeing and these are linked to the inputs of the teachers and the education environment as well as the functions of PERKIM’s management structure. The study posits that the direction of the model must come from the understanding of the Islamic Education Philosophy. It is acknowledged that further study may be required to detail out the the specific elements of the model and this will further add to future scholarly contribution in the area.